Case Report: Novel Mutations in the PCCB Gene Causing Late-Onset Propionic Acidemia - Ji, Guang; Liu, Yaling; Song, Xueqin; Li, Zhenfei (Frontiers in Genetics, 2022)
Introduction: Propionic acidemia is an autosomal recessive metabolic disorder and the patients with adult onset are very rare. Methods: Two PCCB mutations were identified. Clinical data were collected from a patient, and metabolic screening and clinical exome sequencing analysis were performed. Results: Two novel mutations were identified in the PCCB gene: M1:c.404_406del:p.G135del and M2:c.632C>T:p.T211I. Conclusion: Late-onset propionic acidemia should be taken into account, and metabolic screening as well as gene analysis should be performed to make a definite diagnosis timely.